The International Criminal Court : a Global Civil Society Achievement. - Glasius, Marlies (Taylor & Francis Ltd., 2005)
A new examination of the International Criminal Court (ICC) from a political science and international relations perspective. It describes the main features of the court and discusses the political negotiations and the on-going clashes between those states who oppose the court, particularly the United States, and those who defend it.